Successful Treatment of a Veteran Suffering from Post-Traumatic Stress Disorder due to War Using Eye Movement Desensitization and Reprocessing a Case Report - M. Behnammoghadam; S. Rahimi Mahmoud Abad; A. Behnammoghadam (Afarand Scholarly Publishing Institute, 2014)
Aims: Post-traumatic stress disorder is an anxiety disorder that occurs in people who have been exposed to psychological traumatic events. The aim of this study was to report the successful treatment of a veteran, suffering from post-traumatic stress disorder due to war using eye movement desensitization and reprocessing method. Patient & Methods: In this case report, the patient was a 46 year old married male with four children sufferring from post-traumatic stress disorder caused by the war, including mental flashback to the event, mental numbness, avoidance and hyper motivation. The patient was treated with 3 sessions of eye movement desensitization and reprocessing. Diagnosis and post-traumatic stress disorder grading scale, the scale relating to mental distress and validity of cognitions scale were used to data collection. Findings: Post-traumatic stress disorder symptoms declined in the patient and therapeutic results was stable in 6 months follow up. Conclusion: Eye movement desensitization and reprocessing method is effective in reducing the symptoms of post-traumatic stress disorder due to war.